1951
DOI: 10.1085/jgp.34.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Synthesis in Mustard Gas-Treated E. Coli B

Abstract: It was shown earlier (1) that E. coli B treated with dilute (1-5 X 10 ~ ~) aqueous solutions of mustard gas [bis(O-chloroethyl)sulfide] are unable to divide, yet their virus-forming capacity is unimpaired. Bodenstein and Kondritzer (2) have observed that the nitrogen mustard N-methyl-bis(O-chloroethyl )-amine blocks the desoxypentose nucleic acid (DNA) formation of amphibian embryos without altering the formation of pentose nucleic acid (PNA). Since the viruses that have been produced by mustard-treated coli a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1953
1953
1966
1966

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…As a result the cells enlarge but lose their ability to divide and eventually die possibly as a consequence of "unbalanced growth," (Barner and Cohen, 1954). This observed pattern, whereby DNA synthesis is inhibited while RNA and protein synthesis continues, has been reported for E. coli subjected to ultraviolet (Kanazir and Errera, 1954;Kelner, 1953) and ionizing radiations (Doudney, 1956), nitrogen mustards (Harold and Ziporin, 1958) and sulfur mustards (Harold and Ziporin, 1958;Herriott, 1951;Pardee, 1954).…”
Section: Discussionsupporting
confidence: 67%
“…As a result the cells enlarge but lose their ability to divide and eventually die possibly as a consequence of "unbalanced growth," (Barner and Cohen, 1954). This observed pattern, whereby DNA synthesis is inhibited while RNA and protein synthesis continues, has been reported for E. coli subjected to ultraviolet (Kanazir and Errera, 1954;Kelner, 1953) and ionizing radiations (Doudney, 1956), nitrogen mustards (Harold and Ziporin, 1958) and sulfur mustards (Harold and Ziporin, 1958;Herriott, 1951;Pardee, 1954).…”
Section: Discussionsupporting
confidence: 67%
“…This was interpreted as indicating development of the phage. Herriot (1951) found that nitrogen mustard inhibited desoxyribose nucleic acid synthesis more than ribose nucleic acid synthesis in E. coli. It would be of interest to know the effect of reactivating light on this reaction.…”
Section: Discussionmentioning
confidence: 96%
“…Experimental Details Preparation of _Phage.--The methods of preparing, purifying (17), and fitering (39) phage have already been discussed.…”
Section: Discussionmentioning
confidence: 99%